Violence and self-esteem among pregnant women in a district of Callao: Violencia y autoestima en gestantes de un distrito del Callao - Morales, Juan (2019)
Objective: Determine the frequency of violence and its relationship with self-esteem level in pregnant women. Materials and methods: Cross-sectional descriptive study. The pregnant women treated at the Healthcare Center of the district of “Mi Peru”, in the Callao Region, constituted the study population. Results: In total, 210 pregnant women participated with a mean age of 25.94 years (SD = 5.94; Range: 14 to 43), the majority between 20 and 30 years of age, 22.9% (n = 48) were victims of physical violence at least once in their lives and 2.9% (n = 6) in the present pregnancy. Psychological violence at least once in their lives occurred in 28.1% (n = 59), while in the present pregnancy it was reported in 8.1% (n = 17). Regarding sexual assault, 8.6% (n = 18) reported the occurrence at least once in their lives and 0.5% (n = 1) in the last pregnancy.   Of the sample, 72.9% (n = 153) presented high self-esteem, 25.7% (n = 54) medium self-esteem and 1.4% (n = 3) low self-esteem. No differences were found between self-esteem level and the history of violence. Conclusions: Physical, psychological and sexual violence is common among women, and pregnancy is not a protective factor. The concurrence of psychological and physical violence is frequent; in both cases the victimizer was an ex-partner.                                                                  Keywords: Violence against women; physical violence; psychological violence; Peru (Source: MeSH, NLM).